A prospective study of causes of death in rural Gadchiroli, an underdeveloped district of India (2011-2013) - Yogeshwar Kalkonde; Mahesh Deshmukh; Sujay Kakarmath; Jyoti Puthran; Vaibhav Agavane; Vikram Sahane; Abhay Bang (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Reliable information on causes of death to understand health priorities is rare from rural underdeveloped regions of India but is needed to direct health care response. This prompted us to study causes of death in a rural region of Gadchiroli, one of the most underdeveloped districts of India. # Methods Data on causes of death were collected from 86 villages between April 2011 and March 2013 using verbal autopsies. Two physicians independently assigned cause of death using the tenth revision of the International Classification of Disease and disagreement was resolved by a third physician. # Results There were 1599 deaths over 188,308 person years of observation. The crude death rate was 8.5 (95% confidence interval (CI)=8.1-8.9). The five leading causes of death were diseases of the circulatory system (20.8%), stroke being the leading cause (14.3%), infections and parasitic disorders (18.4%), injuries and other external causes of mortality (10%), peri-natal diseases (6.5%) and diseases of the respiratory system (6.4%). Non-communicable diseases (NCDs) accounted for 38.5%, infections and perinatal diseases for 28.3% and external causes including injuries for 10% of all deaths. # Conclusions Epidemiological transition with a shift in causes of deaths from communicable to NCDs has occurred even in a rural underdeveloped district like Gadchiroli. Public health system in rural India which focuses on infections and maternal and child health will now need to be strengthened urgently to face the triple challenge of communicable and non-communicable diseases as well as injuries.